Molecular Detection and Antibiogram of ESBL-Producing and Carbapenem-Resistant Escherichia coli from Rabbit, Swine, and Poultry in Malaysia - M. H. Chai; M. Z. Sukiman; N. Jasmy; N. A. Zulkifly; N. A. S. Mhd Yusof; N. M. Mohamad; S. M. Z. Ariffin; M. F. Ghazali (Faculty of Animal Science, Bogor Agricultural University, 2022)
The emergence of multidrug-resistance Enterobacteriaceae such as extended-spectrum β-lactamase (ESBL) producing Escherichia coli (E. coli) and carbapenem-resistant E. coli (CREC) has become an urgent veterinary and public health threat. These multidrug-resistant microorganisms are frequently associated with diseases that have high mortality with limited treatment options. This study aims to investigate the prevalence of ESBL producing E. coli and CREC from the rabbit, swine, and poultry and to determine the antibiogram profile of these E. coli isolates. In this study, 400 fecal swab samples were collected from rabbits, swine, and poultry from several selected animal farms in Malaysia. After incubation and isolation processes, suspected E. coli isolates were subjected to a PCR test to confirm the identity of the bacteria. The antibiogram of the E. coli isolates was determined via the Kirby Bauer disk diffusion method. A total of 212 (53%) E. coli isolates were isolated from rabbits (51 isolates), poultry (110 isolates), and swine (51 isolates). Screening of antimicrobial resistance genes revealed twelve ESBL producing E. coli (3%; 12/400). Two ESBL producing E. coli were also carrying carbapenemase gene (BlaNDM), indicating ESBL producing and carbapenem-resistant E. coli (ESBL-CREC) in poultry fecal swab samples. The bacteria isolates were found to show resistance against nine antibiotics, including ertapenem, ampicillin, and amoxicillin-clavulanate. A total of 3.3% (7/212) of the E. coli isolates were found to be multidrug-resistance. This study demonstrated the presence of ESBL-producing E. coli and ESBL-producing CREC from poultry fecal swabs in Malaysia.